39.6k views
5 votes
How do you do the elimination method? Example: -8+6y=2;16x-3y= -13

(click on picture to see the full thing)

How do you do the elimination method? Example: -8+6y=2;16x-3y= -13 (click on picture-example-1

2 Answers

1 vote
I will attach the picture
first step is to multiply the first equation by 2
How do you do the elimination method? Example: -8+6y=2;16x-3y= -13 (click on picture-example-1
User SLearner
by
6.0k points
1 vote
Double the first equation to get
-16x+12y=4

Add that to the second equation and get
9y=-9
y=-1

Then we solve for x. Let's plug y into the first equation.
-8x+6y=2
-8x-6=2
-8x=8
x=-1

y=-1
x=-1
User Ankush Soni
by
5.7k points